ANALISIS IMPLEMENTASI BUDAYA KINERJA 5R DALAM UPAYA OPTIMALISASI DAN PENINGKATAN MUTU PELAYANAN OPERASIONAL PADA UNIT RAWAT JALAN RSUD JENDERAL AHMAD YANI METRO - Maya Aprilianingsih; Fina Maharani Putri; Alfian Syahrul Purnama; Nazwa Eleanora (Journal of Hospital Administration and Excellent Health Service, 2026)
Introduction: The 5R culture (Sort, Set in order, Shine, Standardize, Sustain) is an essential approach to creating an efficient, orderly, and safe hospital work environment. However, its implementation in high-activity service units is often inconsistent and sub-optimal. This study aims to analyze the implementation of the 5R culture in the Outpatient Unit of RSUD Jenderal Ahmad Yani Metro. Method: This study utilized a qualitative descriptive approach through direct observation, in-depth interviews with healthcare and administrative staff, and Focus Group Discussions (FGD) during Field Learning Practices. Problem prioritization was analyzed using the Urgency, Seriousness, Growth (USG) method. Result: The results indicated that the implementation of 5R principles in the outpatient unit has been inconsistent. Based on the USG analysis, the lack of 5R implementation emerged as the top priority with the highest score (14). The dominant causes hindering optimal 5R execution are limited storage infrastructure and a high daily patient workload, even though basic SOPs and supervision are already in place. Conclusion: Improving the 5R culture in the Outpatient Unit requires optimization through physical storage upgrades, visual management standardization, routine monitoring enforcement, and a structured reward and punishment scheme.